LEGAL STUDY ON THE IMPLEMENTATION OF CLOSE SUPERVISION BASED ON PERKAP NO. 2 OF 2022 AT THE DELI SERDANG CITY POLICE - Gusti Abi Mahyu; Syahrul Bakti Harahap (Jurnal Ilmu Hukum dan Keadilan, 2026)
This study aims to examine the implementation of inherent supervision based on Regulation of the Chief of the Indonesian National Police Number 2 of 2022 at the Deli Serdang City Police, to identify factors that hinder its effectiveness, and to formulate solutions to violations occurring in its implementation. The implementation of inherent supervision based on Regulation Number 2 of 2022 at the Deli Serdang City Police has, in principle, been carried out in accordance with the applicable normative provisions. Supervision is conducted by direct superiors through guidance, monitoring, evaluation, and coaching of subordinates. The mechanism of inherent supervision has been implemented in a tiered manner and emphasizes a preventive approach as regulated in the Regulation. Nevertheless, its implementation has not been fully consistent and continuous across all work units. This indicates that although the Regulation has been used as a guideline, its implementation still requires strengthening. Solutions to violations of Regulation Number 2 of 2022 at the Deli Serdang City Police can be pursued through strengthening guidance, increasing consistency in supervision, and enforcing discipline in a tiered and proportional manner.